(untitled) (Asian Journal of Medical and Biological Research, 2015)
The effects of feeding probiotic (PB) with or without Lincomycin 2.2% (AGP) were investigated in broiler chickens during summer. Seven hundred Cobb-500 one day old straight run broiler chicks were randomly distributed into four dietary treatments each of five replications. Four diets were compared: control; control diet plus PB (Bacillus subtilis DSM17299) at a level of 50g/100kg; control plus (AGP) at a level of 15g/100kg and control plus a combination of PB and AGP (50gm/100kg and 15g/100kg respectively). Control birds were fed on a corn-soybean based starter mash that contained ME 3000 kcal/kg and CP 24.39% from 0-21 days of age and a corn-soybean based grower mash of ME 3100 kcal/kg and CP 20.43% during 22-35 days of age. The records were kept of feed intake (FI), body weight and mortality while weight gain, feed conversion ratio (FCR) and survivability were calculated. Temperature and humidity were recorded four times daily except during extreme heat stress when measurements were made more frequently. One bird that was close to average of pen weight was taken from each replication at the end of the trial and the birds were sacrificed to determine carcass characteristics. Both performance and carcass yield data were statistically analyzed. Birds that received PB and a combination of PB +AGP treatments showed significant differences (P<0.01) from control with respect to body weight gain and FCR while feeding AGP alone although showed a decrease in feed intake. Abdominal fat was significantly (P<0.01) reduced in PB treated birds. Higher mortality was encountered in control group. Both PB alone and a combination of AGP treatments were able to show improved performance and reduced mortality, feeding PB alone may be practiced on the combined grounds of improved performance, efficiency in combating heat stress and to discourage the use of AGP in broiler diet. Asian J. Med. Biol. Res. June 2015, 1(1): 80-88